Staff Nurses' Perceptions and Experiences about Structural Empowerment: A Qualitative Phenomenological Study. - Peter Van Bogaert (PLoS ONE, 2016)
The aim of the study reported in this article was to investigate staff nurses' perceptions and experiences about structural empowerment and perceptions regarding the extent to which structural empowerment supports safe quality patient care. To address the complex needs of patients, staff nurse involvement in clinical and organizational decision-making processes within interdisciplinary care settings is crucial. A qualitative study was conducted using individual semi-structured interviews of 11 staff nurses assigned to medical or surgical units in a 600-bed university hospital in Belgium. During the study period, the hospital was going through an organizational transformation process to move from a classic hierarchical and departmental organizational structure to one that was flat and interdisciplinary. Staff nurses reported experiencing structural empowerment and they were willing to be involved in decision-making processes primarily about patient care within the context of their practice unit. However, participants were not always fully aware of the challenges and the effect of empowerment on their daily practice, the quality of care and patient safety. Ongoing hospital change initiatives supported staff nurses' involvement in decision-making processes for certain matters but for some decisions, a classic hierarchical and departmental process still remained. Nurses perceived relatively high work demands and at times viewed empowerment as presenting additional. Staff nurses recognized the opportunities structural empowerment provided within their daily practice. Nurse managers and unit climate were seen as crucial for success while lack of time and perceived work demands were viewed as barriers to empowerment.